Microbes affect gut epithelial cell composition through immune-dependent regulation of intestinal stem cell differentiation. - Liu, X.; Nagy, P.; Bonfini, A.; Houtz, P.; Bing, X.L.; Yang, X.; Buchon, N. (Cell reports, 2022)
Gut microbes play important roles in host physiology; however, the mechanisms underlying their impact remain poorly characterized. Here, we demonstrate that microbes not only influence gut physiology but also alter its epithelial composition. The microbiota and pathogens both influence intestinal stem cell (ISC) differentiation. Intriguingly, while the microbiota promotes ISC differentiation into enterocytes (EC), pathogens stimulate enteroendocrine cell (EE) fate and long-term accumulation of EEs in the midgut epithelium. Importantly, the evolutionarily conserved Drosophila NFKB (Relish) pushes stem cell lineage specification toward ECs by directly regulating differentiation factors. Conversely, the JAK-STAT pathway promotes EE fate in response to infectious damage. We propose a model in which the balance of microbial pattern recognition pathways, such as Imd-Relish, and damage response pathways, such as JAK-STAT, influence ISC differentiation, epithelial composition, and gut physiology.